ANALISA PERHITUNGAN KEBUTUHAN DEBIT AIR DI WILAYAH PELAYANAN BOOSTER KERTAPATI - Delli Noviarti Rachman; Rudi Yansah (UNIVERSITAS INDO GLOBAL MANDIRI, 2020)
To improve clean water distribution services in an area, several steps must be considered. This step is to calculate the available water supply, then calculate the projected population growth until the end of the planning year and calculate the need for clean water in Kertapati District. PDAM Tirta Musi, especially the Kertapati booster which is in the service area opposite Ulu 1, is the agency responsible for providing clean water for residents in the service area of Kertapati District. However, currently PDAM services are still 50.87% of the total population of Kertapati District. After conducting the research, the results of the water supply received from the Ogan IPA were 90.47 liters / second or 7,816 m3 / day, when compared to the supply needed to serve the community's clean water needs in the Kertapati Booster service area in 2018 plus a number leakage of 89.54 liters / second or 7,736 m3 / day. With a service level of 50.87% of the population. Meanwhile, the water supply that must be provided to serve all the water needs of the people of Kertapati District is 176.01 liters / second or 15,207 m3 / day and at the end of the planning year it is 235.73 liters / sec or 20,367 m3 / day. It can be concluded that for the projection in 2027 the available water supply will not be able to serve daily water needs for 24 hours